Evaluasi Kinerja Operasional Pelayanan Angkutan Perkotaan Trayek K-18 (Terminal Cikarang – Sukatani) di Kabupaten Bekasi - Suganda, Riyan; RR, R. Caesario Boing; Anggraini, Ekhty Putri; Nurhanifah, Hasna (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Urban public transportation plays an important role in supporting community mobility as well as economic and social activities in urban areas. Route K-19, which serves the Terminal Bekasi–Mutiara Gading Timur corridor, is one of the strategic transportation modes for residents of East Bekasi and Mustikajaya. Along with the continuous growth of the population, an evaluation of the service quality of this route is necessary to ensure the effectiveness and efficiency of its operational performance.This study aims to analyze the operational performance of Route K-19 based on several indicators, namely load factor, frequency, headway, speed, and circulation time, which are used to determine the required number of vehicles. The research method used is a quantitative approach through field surveys conducted during peak and off-peak hours. The data collected include vehicle frequency, the number of boarding and alighting passengers, route distance, and travel time.The data were analyzed by comparing the actual operational performance with the existing urban public transportation service standards and by determining the number of vehicles required to improve the operational performance of the public transport system. The main problems found on this route include relatively long passenger waiting times and irregular headways due to the absence of a fixed scheduling system, as well as the impact of traffic congestion on travel speed. Therefore, better fleet arrangement and improved operational management are needed to enhance service quality.